Transformation of Women Status through Self- Help Groups in Pudukkottai Block - Dr. N. Rameshkumar (International Journal of Engineering and Management Research, 2018)
The rural area peoples are mostly suffered of human life style because it is based on the reason of economic. The present study focused area of psychological, social and economic empowerment of women in Pudukkottai block specified rural area of Perungalur, Athanakottai, Varapur, Mullur and Vadavalam. It is; therefore, women need special attention to ensure their development and active participation in the decision-making process at home. It is also widely recognized that apart from managing household, bearing children, rural women bring income with productive activities ranging from traditional work in the fields to working in factories or running small and petty businesses. They have also proven that they can be better entrepreneurs and development managers in any kind of human development activities. The empowerment of women also considered as an active process enabling women to realize their full identity and power in all spheres of life. The empowerment of women is modified in our life with help of Self Help Groups in Pudukkottai area.